Socially Responsible Higher Education International Perspectives on Knowledge Democracy - Hall, Budd L.; Tandon, Rajesh (Brill, 2021)
Is higher education contributing to our global crises? Does it offer stories of hope? The editors feature authors and viewpoints from often excluded groups of emerging scholars and parts of the world seldom read in literature on higher education and social responsibility.; Readership: Higher education students, scholars and administrators. Ministries of higher education, policy makers, networks, foundations, UNESCO World Conference on Higher Education, Climate crisis and social justice activists, University World News.